PENGGUNAAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR IPA MATERI SISTEM PERNAPASAN PADA MANUSIA DI KELAS V SD INPRES KOBELETE - Imanuel Y Faot (STKIP Subang, 2024)
This research aims to improve student learning outcomes on human respiratory system material in class V of SD Inpres Kobelete. Science learning requires students to understand the natural surroundings and discover concepts from the material being studied. Therefore, teachers must be creative in designing learning that is able to increase student understanding. One way is by including technology in learning in the form of audio-visual media. This research is classroom action research which is designed in 2 cycles and 1 meeting in each cycle. The design used is according to Kurt Lewin which consists of four stages, namely planning, acting, observing and reflecting. The focus of the research was all fifth grade students at SD Inpres Kobelete, totaling 28 students and consisting of 14 male students and 18 female students. The research instruments used were teacher activity observation sheets, student activity observation sheets and learning outcomes test questions. Student learning outcomes increased from pre-cycle, only 12.5% ​​of students met the KKM, increasing to 81.25% in cycle I and 100% in cycle II. Thus, the results of this study conclude that the use of audio-visual media has been proven to improve student learning outcomes.